Fragment Library of Colombian Natural Products: Generation and Comparative Chemoinformatic Analysis - Ana L. Chávez-Hernández; Johny R. Rodríguez-Pérez; Héctor F. Cortés-Hernández; Hoover A. Valencia-Sanchez; Miguel Á. Chávez-Fumagalli; José L. Medina-Franco (Drugs and Drug Candidates)
Fragment libraries have a major significance in drug discovery due to their role in de novo design and enumerating large and ultra-large compound libraries. Although several fragment libraries are commercially available, most are derived from synthetic compounds. The number of fragment libraries derived from natural products is still being determined. Still, they represent a rich source of building blocks to generate pseudo-natural products and bioactive synthetic compounds inspired by natural products. In this work, we generated and analyzed a fragment library of natural products from Colombia, a highly diverse geographical region where fragment libraries are yet to be reported. We also generated and reported fragment libraries of three novel natural product libraries and, as a reference, the most updated version of FDA-approved drugs. In line with the principles of open science, the fragment libraries developed in this study are freely available.